Design and analysis of dual-mode numerically controlled oscillators based controlled oscillator frequency modulation - Ramana Reddy Gujjula; Chitra Perumal; Prakash Kodali; Bodapati Venkata Rajanna (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In this paper, the design and analysis of dual-mode numerically controlled oscillators (NCO) based controlled oscillator frequency Modulation is implemented. Initially, input is given to the analog to digital (ADC) converter. This will change the input from analog to digital converter. After that, the pulse skipping mode (PSM) logic and proportional integral (PI) are applied to the converted data. After applying PSM logic, data is directly transferred to the connection block. The proportional and integral block will transfer the data will be decoded using the decoder. After decoding the values, it is saved using a modulo accumulator. After that, it is converted from one hot residue (OHR) to binary converter. The converted data is saved in the register. Now both data will pass through the gate driver circuit and output will be obtained finally. From simulation results, it can observe that the usage of metal oxide semiconductor field effect transistors (MOSFETs) and total nodes are very less in dual-mode NCO-based controlled oscillator frequency modulation.